Pain in Parkinsons Disease: from the Pathogenetic Basi441;s to Treatment Principles (Global Journal of Medical Research, 2020)
Pain syndromes are quite common in Parkinson s disease in addition to the motor defect can significantly worsen the quality of life Various types of pain related to PD have been described Different clinical characteristics of the pain variable relationship with motor symptoms and variable response to dopaminergic drugs as well as in some cases the dependence its appearance in a specific time of the day suggest that pain in PD has a complex mechanism with the widespread impairment of the sensory information transmission at different levels of the CNS In addition to the dopaminergic systems of the brain and spinal cord non-dopaminergic systems nor epinephrine serotonin
Keywords: pain; parkinson's disease; nociceptive pathway; basal ganglia; non motor symptoms; noradrenergic system